1997
DOI: 10.1006/jabr.1997.7088
|View full text |Cite
|
Sign up to set email alerts
|

Groups Satisfying Semigroup Laws, and Nilpotent-by-Burnside Varieties

Abstract: We investigate the structure of groups satisfying a positi¨e law, that is, an identity of the form u '¨, where u and¨are positive words. The main question here is whether all such groups are nilpotent-by-finite exponent. We answer this question affirmatively for a large class C C of groups including soluble and residually finite groups, showing that moreover the nilpotency class and the finite exponent in question are bounded solely in terms of the length of the positive law. It follows, in particular, that if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 18 publications
2
65
0
Order By: Relevance
“…In accordance with the theorem by Burns, Macedońska and Medvedev [2] there exist n-bounded numbers c and e such that for any a ∈ A # the centralizer C G (a) is an extension of a nilpotent group of class at most c by a group of exponent dividing e. By Lemma 2.8 we conclude that the exponent of the quotient G/F (G) is {e, q}-bounded. Let {p 1 , .…”
Section: L(g H) Is Always a Subalgebra Of Dl(g)supporting
confidence: 77%
See 1 more Smart Citation
“…In accordance with the theorem by Burns, Macedońska and Medvedev [2] there exist n-bounded numbers c and e such that for any a ∈ A # the centralizer C G (a) is an extension of a nilpotent group of class at most c by a group of exponent dividing e. By Lemma 2.8 we conclude that the exponent of the quotient G/F (G) is {e, q}-bounded. Let {p 1 , .…”
Section: L(g H) Is Always a Subalgebra Of Dl(g)supporting
confidence: 77%
“…In contrast with this negative result, Burns, Macedońska and Medvedev answered the question in the affirmative for a large class of groups including all solvable and residually finite groups [2]. In particular they showed that there exist functions c(n) and e(n) of n only, such that any finite group satisfying a positive law of degree n is an extension of a nilpotent group of class at most c(n) by a group of exponents dividing e(n).…”
Section: Introductionmentioning
confidence: 93%
“…In fact [1] gives in essence a characterization of words w yielding the conclusion of our Theorem A, but in terms of the form of w itself. However the results of [1,2,3] depended ultimately on a lemma of Shalev [20 [5] Group laws implying virtual nilpotence 299 apart from the improvements claimed for the results of the present paper over those of [1,2,3], it is also justified by the need to provide arguments based on the corrected version of Shalev's lemma. Nevertheless the arguments we use, although mostly self-contained, are to a considerable extent adapted from those of Shalev [20], as well as [1,2,15].…”
Section: Dichotomy Theorem (For Words Of F) Letw E Fbean Arbitrary Wmentioning
confidence: 65%
“…From this assumption and the law (13) which our p-group G satisfies, it follows that G satisfies a law of the form (14) where p 3 is a product of commutators in x and y (from F (2) ) of weights > c. We now impose a further lower bound on p, assuming in addition that p > e 4 .…”
Section: Subcase: P Sufficiently Large This Subcase Concerns Primes mentioning
confidence: 99%
“…It follows now from results of Kim and Rhemtulla ([5] Theorem A and Lemma 3), that G must be locally -(polycyclic-by-finite). Since G is soluble-by-finite and satisfies a positive law of degree n, then by ( [9], Theorem B), G must be periodic extension of a nilpotent group. In particular G ∈ N c B e , where c and e depend on n only, which finishes the proof.…”
Section: Problemsmentioning
confidence: 99%